Ecological resources used by Xylocopa species (Apidae: Xylocopini) in the urban area - CHAVES-ALVES, TALLES MARQUES; JUNQUEIRA, CAMILA NONATO; SOUZA-RABELO, LAÍCE; MACEDO DE OLIVEIRA, PAULO EUGÊNIO ALVES; AUGUSTO, SOLANGE CRISTINA (Revista Colombiana de Entomología, 2011)
Green areas of cities such as ecological parks, squares, road forestation and even domestic gardens, besides being part of the urban landscape, also serve as ecological resources for many bee species, as those belonging to Xylo- copa genus. In this sense, the present study aimed to identify the natural nesting substrates and food resources available for Xylocopa spp. in order to verify the management potential of these bees in an urban area. Additionally, we observed the percentage of occupancy for these bees on previously available substrates (trap-nests). Three plants were used as nesting substrates: Spathodea campanulata (Bignoniaceae), Ligustrum lucidum (Oleaceae) and Ficus sp. (Moraceae). The nests presented an aggregated distribution. Spathodea campanulata, Ficus sp. and bamboo canes (trap-nests) were considered efficient substrates for Xylocopa spp. nesting and, for this reason, they can be used in management and con- servation of these bees. The flowers of the few trees species visited by Xylocopa in urban areas belong to groups often associated with bees and the food sources were different from those species used for nesting. The urban environment under appropriate conditions, when appropriate nest substrates and food sources are presented, can serve as a place for study, conservation and management of carpenter bees.